Horizontal gene transfer : Generating antibiotic resistant bacteria - Mohamad Amin Bin Awang Teh @ Ismail (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
This study aspires to understand gene mobility and its benefits. The process of gene mobility is known as horizontal gene transfer (HGT) in which the HGT consist of three different modes acknowledged as transduction, transformation and conjugation. The obvious benefit from HGT is that gene can be obtained from different progenies that deviates from Darwinian Theory of gene tree. Therefore, this study focuses on conjugation since the event of gene transfer to follow conjugation is more likely to occur in nature. Conjugation is a simple natural occurrence where cell-to-cell contact takes place for gene transfer. The gene sequence that is analyzed in this study is antimicrobial resistant gene responsible for tetracycline resistant. Antimicrobial susceptibility test is determined to be the standard gold test compared to analytical colony polymerase chain reaction (PCR) method. There are two methods used for conjugation experiment which are plate and broth mating. The analysis of conjugation follows statistical analysis where events of probability across time intervals is tabulated in table of spectroscopy value with highest value at 0.4321. Hence, using hypothesis testing, broth mating is accredited to be better that plate mating as a claim at 95% confidence interval that gives value of Z normal test at 4.4923.